1994
DOI: 10.1159/000133813
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the entire FL11 gene, disrupted by the Ewing’s Sarcoma translocation breakpoint on 11q24, in a yeast artificial chromosome

Abstract: FLU (Friend leukemia virus integration 1), a member of the Ets gene family, is disrupted on llq24 by the Ewing’s Sarcoma (ES) and Peripheral Neuroepithelioma (PNE) t(11;22)(q24;q12) translocation. ES and PNE are Primitive Neuroectodermal Tumors (PNETs) and the consistent translocation t(11;22)(q24;q12) can be used for differential diagnosis. In PNETs the 3’ part of human FLU is translocated from 11q24 to 22q12, where it is juxtaposed to the 5’ end of the Ewing’s Sarcoma gene (EWS). A fusion transcript, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Pulse-®eld gel analysis has localized the Fli-1 gene within 240 kb of the Ets-1 locus on mouse chromosome 9 and on human chromosome 11q23, suggesting that these two ets genes arose by gene duplication from a common ancestral gene (Ben-David et al, 1991a;Watson et al, 1992). Human Fli-1 contains nine exons which extend over approximately 120 kb (Selleri et al, 1994). A comparison of the amino acid sequences of Fli-1 revealed an 81% homology to the ets-related protein Erg-2 (Prasad et al, 1992).…”
Section: Fli-1 Characteristics and Its Position Amongst Other Ets Genesmentioning
confidence: 99%
“…Pulse-®eld gel analysis has localized the Fli-1 gene within 240 kb of the Ets-1 locus on mouse chromosome 9 and on human chromosome 11q23, suggesting that these two ets genes arose by gene duplication from a common ancestral gene (Ben-David et al, 1991a;Watson et al, 1992). Human Fli-1 contains nine exons which extend over approximately 120 kb (Selleri et al, 1994). A comparison of the amino acid sequences of Fli-1 revealed an 81% homology to the ets-related protein Erg-2 (Prasad et al, 1992).…”
Section: Fli-1 Characteristics and Its Position Amongst Other Ets Genesmentioning
confidence: 99%
“…To ascertain the involvement of the FLI1 gene at 11q24, cosmids flanking or overlapping the breakpoint region EWS-R2 were hybridized in different studies [18][19][20][21][22]. Also, yeast artificial chromosome (YAC) probes are available for 3.2 Mb of DNA within band 11q24 including the entire FLI1 gene, thus providing new DNA probes for detection of rearrangements involving this chromosomal region [23,24]. Simultaneous hybridization of probes located proximally to the EWS breakpoint region on chromosome 22 and distally to the FLI1 gene on chromosome 11 identifies the fused breakpoint regions of the classical t(11;22)(q24;q12).…”
Section: Q12 Rearrangements Visualized By Doubletarget Fishmentioning
confidence: 99%
“…1,2,[11][12][13] The human homologs of many of these genes including FLI-1, PU.1, ETS-1, ETS-2, ELK-1 and K562, HEL, and CRL9078 (PA317) cells were purchased from ELK-2, have been mapped to chromosomal regions known to the American Type Culture Collection; CRE cells were be involved in translocations characteristic of specific leukeobtained from Dr R Mulligan; K562 and HEL were cultured mias, lymphomas, and other tumors. [14][15][16][17][18][19][20][21][22][23][24][25] in RPMI medium supplemented with 10% fetal bovine serum Many of the ETS genes are known to be expressed in hema-(FBS) plus antibiotics (Atlanta Biological, Atlanta, GA, USA); topoietic tissues and cell lines. [26][27][28][29][30][31] It was demonstrated that CRE and PA317 cells were cultured in Dulbecco's MEM supthe PU.1 gene product is essential for the normal development plemented with antibiotics and 8% calf serum or 10% FBS, of myeloid and B lymphoid lineages, 32 while inactivation of respectively.…”
mentioning
confidence: 99%